Addressing glycan and hematological barriers in pig-to-nonhuman primate liver xenotransplantation: challenges and future directions - Jae Young Kim (Clinical Transplantation and Research)
Achieving long-term survival in pig-to-primate liver xenotransplantation has proven highly challenging due to significant hematological issues. This paper investigates the primary obstacles from a hematological perspective, focusing on coagulation disorders caused by molecular incompatibility between species. It also examines the mismatched glycan structures on the surfaces of platelets and red blood cells, which lead to sequestration and phagocytosis by recipient macrophages. These mismatches underscore the need for improved glycan and molecular compatibility to overcome immunological and physiological barriers. Moreover, the liver's unique role in synthesizing a wide array of proteins, especially those involved in blood coagulation, introduces additional challenges of molecular incompatibility compared to other organs, such as the heart and kidneys. This study highlights the importance of addressing these challenges to improve the outcomes of liver xenotransplantation and suggests the necessity of strategies like glycan matching and the development of gene-edited pigs specifically tailored for liver transplantation.